2023
DOI: 10.1002/ccd.30630
|View full text |Cite
|
Sign up to set email alerts
|

Effects of delayed hospitalization on the 3‐year clinical outcomes of patients with or without diabetes who had non‐ST‐segment‐elevation myocardial infarction and underwent new‐generation drug‐eluting stent implantation

Abstract: Clinical outcomes after non‐ST‐segment‐elevation myocardial infarction (NSTEMI) in patients with (symptom‐to‐door time [SDT] ≥ 24 h) or without (SDT < 24 h) delayed hospitalization among patients with or without diabetes were compared. From the Korea Acute Myocardial Infarction Registry‐National Institute of Health, a total of 4517 patients with NSTEMI who underwent new‐generation drug‐eluting stents implantation were recruited and they were classified into the diabetes mellitus (DM) and non‐DM groups. These t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 42 publications
0
0
0
Order By: Relevance
“…Given that HbA1c reflects the cumulative glycemic status of the recent 2–3 months [ 32 ], these observations suggest that the mortality benefits of early presentation seem to be attenuated under the circumstance with poor glycemic control. It seems to be in line with a previously published study, which demonstrated no prognostic difference between patients with diabetes with and without SDT prolongation [ 33 ]. These similarities on all-cause mortality at a higher HbA1c level may be moderately explained by the fact that dysglycemia itself contributes to high rates of adverse cardiovascular outcomes, including mortality [ 34 ], and result in greater infarct sizes [ 34 ].…”
Section: Discussionsupporting
confidence: 92%
“…Given that HbA1c reflects the cumulative glycemic status of the recent 2–3 months [ 32 ], these observations suggest that the mortality benefits of early presentation seem to be attenuated under the circumstance with poor glycemic control. It seems to be in line with a previously published study, which demonstrated no prognostic difference between patients with diabetes with and without SDT prolongation [ 33 ]. These similarities on all-cause mortality at a higher HbA1c level may be moderately explained by the fact that dysglycemia itself contributes to high rates of adverse cardiovascular outcomes, including mortality [ 34 ], and result in greater infarct sizes [ 34 ].…”
Section: Discussionsupporting
confidence: 92%